Epigenetic regulation of promiscuous gene expression in thymic medullary epithelial cells - Tykocinski, Lars-Oliver (National Academy of Sciences, 2010)
Thymic central tolerance comprehensively imprints the T-cell receptor repertoire before T cells seed the periphery. Medullary thymic epithelial cells (mTECs) play a pivotal role in this process by virtue of promiscuous expression of tissue-restricted autoantigens. The molecular regulation of this unusual gene expression, in particular the involvement of epigenetic mechanisms is only poorly understood. By studying promiscuous expression of the mouse casein locus, we report that transcription of this locus proceeds from a delimited region (“entry site”) to increasingly complex patterns along with mTEC maturation. Transcription of this region is preceded by promoter demethylation in immature mTECs followed upon mTEC maturation by acquisition of active histone marks and local locus decontraction. Moreover, analysis of two additional gene loci showed that promiscuous expression is transient in single mTECs. Transient gene expression could conceivably add to the local diversity of self-antigen display thus enhancing the efficacy of central tolerance.